The colonial past in history textbooks : historical and social psychological perspectives - Nieuwenhuyse, Karel van; Valentim, Joaquim Pires (International review of history education., 2018)
"This book examines the evolving representations of the colonial past from the mid-19th century up to decolonisation in the 1960s and 70s - the so-called era of Modern Imperialism - in post-war history textbooks from across the world. The aim of the book is to examine the evolving outlook of colonial representations in history education and the underpinning explanations for the specific outlook in different - former colonizer and colonised - countries (to be found in collective memory, popular historical culture, social representations, identity-building processes, and the state of historical knowledge within academia). The approach of the book is novel and innovative in different ways. First of all, given the complexity of the research, an original interdisciplinary approach has been implemented, which brings together historians, history educators and social psychologists to examine representations of colonialism in history education in different countries around the world while drawing on different theoretical frameworks. Secondly, given the interest in the interplay between collective memory, popular historical culture, social representations, and the state of historical knowledge within academia, a diachronic approach is implemented, examining the evolving representations of the colonial past, and connecting them to developments within society at large and academia"--